1985
DOI: 10.1515/bchm3.1985.366.1.479
|View full text |Cite
|
Sign up to set email alerts
|

Human Inter-α-Trypsin Inhibitor: Localization of the Kunitz-Type Domains in the N-terminal Part of the Molecule and their Release by a Trypsin-Like Proteinase

Abstract: The N-terminal amino-acid sequence of human ITI has been found to be identical with that of the acid-stable human 30-kDa inhibitors (HI-30) from urine, serum, and those released from inter-a-trypsin inhibitor by trypsin or chymotrypsin. Serum HI-30 and HI-30 released by trypsin differ from the urinary inhibitor by an additional C-terminal arginine residue.Compared to these two inhibitors the inhibitor released by chymotryptic proteolysis is elongated C-terminally by an additional phenylalanine residue. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Bikunin contains two tandem repeats of Kunitztype domains, and the trypsin inhibitor activity of ITI is localized in this part (23,42). Bikunin is also identified in urine as UTI (urinary trypsin inhibitor), which was shown to be a urine proteoglycan with molecular mass ranging from 40 to 45 kDa (43)(44)(45).…”
Section: Peaksmentioning
confidence: 99%
“…Bikunin contains two tandem repeats of Kunitztype domains, and the trypsin inhibitor activity of ITI is localized in this part (23,42). Bikunin is also identified in urine as UTI (urinary trypsin inhibitor), which was shown to be a urine proteoglycan with molecular mass ranging from 40 to 45 kDa (43)(44)(45).…”
Section: Peaksmentioning
confidence: 99%
“…As shown in figure 3, 125I-UTI in the plasma was excreted into the urine in its intact form. Plasma ASTI is assumed to be a precursor form of UTI based on its immuno logical and physicochemical properties and NH2-terminal amino acid sequence [14][15][16]. The activity of plasma ASTI in renal failure patients was found to be about 20-fold higher than that of normal subjects [14].…”
Section: Excretion Of !25i-labeled Utimentioning
confidence: 99%
“…Further characterization of cDNAs has shown that ITI is composed of distinct heavy chains (heavy chains 1 and 2) that are linked limited proteolysis of ITI in the N-terminal region of the polypeptide chain [4]. UTI is increased in several diseases, including inflammation and cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…More indications regarding the relationship between ITI, UTI, and other polypeptides derived from them have been given elsewhere [3]. The structure of these molecules, their polypeptidic chains, their proteoglycan moiety, the location of proteinase inhibitory sites, as well as the molecular weights are described elsewhere [1][2][3][4]7].…”
Section: Introductionmentioning
confidence: 99%